Tiered healthcare in South Africa exposes deficiencies in management and more patients with infectious etiology of primary adrenal insufficiency - Mofokeng, Thabiso Rafaki Petrus (PLoS One, 2020)
OBJECTIVE: We wished to determine the prevalence, etiology, presentation, and available management strategies for primary adrenal insufficiency (PAI) in South Africa (SA), hypothesizing a prevalence greater than the described 3.1 per million. There is great inequity in healthcare allocation, as two parallel healthcare systems exist, potentially modifying PAI patients’ clinical profiles, private being better resourced than public healthcare. METHODS: An online survey of physicians’ experience relating to PAI. RESULTS: The physicians were managing 811 patients, equal to a prevalence of 14.2 per million. Likely causes of PAI in public/ academic vs private settings included: AIDS-related [304 (44.8%) vs 5 (3.8%); p<0.001], tuberculosis [288 (42.5%) vs 8 (6.0%); p<0.001], autoimmune disease [50 (7.4%) vs 88 (66.2%); p<0.001], malignancy [27 (4.0%) vs 7 (5.3%); p = 0.500], genetic including adrenoleukodystrophy (ALD) [5 (0.7%) vs 16 (12.0%); p<0.001], respectively. Overall, more patients presented with nausea [101 (74.3%) and vomiting 89 (65.9%), than diarrhoea 76 (58.9%); p = 0.008 and 126 (15.5%) in adrenal crisis. Features suggestive of a crisis were hypoglycaemia [40 (78.4%) vs 42 (48.8%); p = 0.001], shock [36 (67.9%) vs 31(36.9%); p<0.001], and loss of consciousness [25 (52.1%) vs 27 (32.9%); p = 0.031]. Greater unavailability of antibody testing in the public vs. the private sector [32 (66.7%) vs 30 (32.1%); p = 0.001], [serum-ACTH 25 (52.1%) vs 16 (19.5%); p<0.001] and glucocorticoids were [26 (54.2%) vs 33 (40.2%); p = 0.015]. Many patients, 389(66.7%) were not using identification, indicating that they need steroids in an emergency. CONCLUSION: A survey of South African physicians suggests a higher prevalence than previously reported. Patients presented with typical symptoms, and 15.5% presented in adrenal crisis. Significant disparities in the availability of physicians’ expertise, diagnostic resources, and management options were noted in the public versus private settings. Greater awareness among health practitioners to timeously diagnose PAI is required to prevent a life-threatening outcome.